Refinement of carbon emission reduction of dockless bike-sharing users’ behavior under different scenarios - Liu, Guanqiu; Zhang, Hao; Cheng, Yu; Qi, Xinhua (Frontiers in Environmental Science, 2025)
IntroductionDockless bike-sharing systems have become popular in urban China. However, how dockless bike-sharing influence users’ daily travel choices has rarely been investigated.Methods Drawing upon travel-related data collected by the day reconstruction method in Fuzhou, this study explores whether and how the mode shift caused by dockless bike-sharing reduces the carbon emission effect in different scenarios.ResultsThe results show that the mode proportion varied before and after the introduction of dockless bike-sharing and affected by travel distance. The carbon emission reduction effect of shared bikes shows an inverted U-shape with the increase of distance, with the carbon emission reduction gain from the medium-distance travel group of 3-5 km being the largest. The unit carbon emission reduction coefficient presents an inverted U-shape rather than a linear rise with distance. The annual personal carbon emission reduction of dockless bike-sharing users is 4,312.42 g and the total in Fuzhou is 33.03 Mt per year.DiscussionThese findings indicate that a improve of the city’s fast cycling lane system can promote the travel mobility and efficiency in the central downtown area.